KINERJA PORTOFOLIO DENGAN METODE SHARP, JENSEN DAN TREYNOR PADA SAHAM INDUSTRI TEKSTIL DI BURSA EFEK INDONESIA - Akhmad Sodikin (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
This study aims to determine portfolio performance using the methods of Sharp, Jensen and Treynor. The companies involved in this study were 18 companies in the industry group of textile which were listed on the Indonesia Stock Exchange in 2016. Data were taken monthly for 12 months. The data is then analyzed to determine the elements needed in the analysis namely market profits, standard deviation of profits (total risk), beta (systematic risk) and risk free profits (risk free). Based on data analysis, it is known that portfolio performance is calculated using 3 methods, namely Sharp, Treynor and Jensen methods in the textile industry stock which includes 18 companies which are mostly negative. However, if it is classified according to non-negative values, then the performance according to the Treynor and Jensen methods can be used as a reference because all of the items that are compared have positive values. According to the Treynor Index shares that can be used as a reference for entry in investments are CNTB, CNTX, ERTX, HDTX and ARGO shares. Meanwhile, according to Jensen's index of shares that can be included in the investment are SSTM, STAR, MYTX and POLY.